1991
DOI: 10.1111/j.1532-5415.1991.tb03576.x
|View full text |Cite
|
Sign up to set email alerts
|

Benign Prostatic Hyperplasia: Pathogenesis and Medical Therapy

Abstract: Epidemiologic studies in castrates strongly support the key role of the testis in the pathogenesis of benign prostatic hyperplasia (BPH). Since the testis secretes androgen and estrogen, both of these hormones have been implicated in BPH. Much information supports the important role of dihydrotestosterone (DHT) in BPH, including intraprostatic activities of enzymes that regulate DHT. Although controversy still exists, DHT levels in BPH may be higher than in normal prostate tissue. Based upon these findings and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 47 publications
0
36
0
1
Order By: Relevance
“…Among these, the following obstacles will be faced by any inhibitor of 5α–reductase: heterogeneity of the disease [106]; coincidental concurrence of human benign prostatic hyperplasia and symptoms unrelated to prostatic enlargement [107]; the effect of residual, or rising testosterone levels on the prostate or prostate size [29], and the possibility that the essential developmental role of DHT in the prostate is not mirrored by regression of the developed, hyperplastic gland on removal of DHT support [108]. …”
Section: Clinical Studiesmentioning
confidence: 99%
“…Among these, the following obstacles will be faced by any inhibitor of 5α–reductase: heterogeneity of the disease [106]; coincidental concurrence of human benign prostatic hyperplasia and symptoms unrelated to prostatic enlargement [107]; the effect of residual, or rising testosterone levels on the prostate or prostate size [29], and the possibility that the essential developmental role of DHT in the prostate is not mirrored by regression of the developed, hyperplastic gland on removal of DHT support [108]. …”
Section: Clinical Studiesmentioning
confidence: 99%
“…For plasma DHT, the majority of case-control investigations suggest that it plays a role in the etiology of BPH [6][7][8], but studies that found no association or even inverse associations have been reported [9,19], The con sensus now is that it is DHT in the end organ rather than in plasma that dominates the pathogenesis of this disease [3,10,12]. For T, some case-control studies found a posi tive association with BPH [7,[20][21][22][23], others found an inverse association [24][25][26], while still others found no association at all [9,18,19,27,28], The fact that surgical castration largely prevents BPH [5,29] implies that T is likely to play a permissive role [12,13], Conflicting are also the results concerning the role, if any, of estrogens in the pathogenesis of BPH. Most of the studies noted posi tive associations [9,20,24,27,28,30,31 ], although these Findings were not always statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Benign prostatic hyperplasia (BPH) and prostate cancer are major causes of morbidity and mortality in the aging male population (Isaacs, 1990;Geller, 1991;Arrighi et al, 1991;Denis and Mahler, 1990;Geller, 1993). The clinical symptoms attributed to BPH occur in the majority of men over the age of 60 and microscopic hyperplasia is a nearly universal finding on autopsy.…”
Section: Pathophysiology Of Dhtmentioning
confidence: 99%
“…BPH is a nonmalignant enlargement resulting from growth of both the stromal and glandular components of the prostate and is the most common neoplastic disease of man (Isaacs, 1990;Geller, 1991). As a consequence of the anatomical location of the prostate, surrounding the urethra just below the bladder, the growth of the prostate can produce difficulty in urination.…”
Section: Pathophysiology Of Dhtmentioning
confidence: 99%